EMIC wave parameterization in the long‐term VERB code simulation. Issue 8 (24th August 2017) - Drozdov, A. Y.; Shprits, Y. Y.; Usanova, M. E.; Aseev, N. A.; Kellerman, A. C.; Zhu, H.
Abstract: Electromagnetic ion cyclotron (EMIC) waves play an important role in the dynamics of ultrarelativistic electron population in the radiation belts. However, as EMIC waves are very sporadic, developing a parameterization of such wave properties is a challenging task. Currently, there are no dynamic, activity‐dependent models of EMIC waves that can be used in the long‐term (several months) simulations, which makes the quantitative modeling of the radiation belt dynamics incomplete. In this study, we investigate Kp, Dst, and AE indices, solar wind speed, and dynamic pressure as possible parameters of EMIC wave presence. The EMIC waves are included in the long‐term simulations (1 year, including different geomagnetic activity) performed with the Versatile Electron Radiation Belt code, and we compare results of the simulation with the Van Allen Probes observations. The comparison shows that modeling with EMIC waves, parameterized by solar wind dynamic pressure, provides a better agreement with the observations among considered parameterizations. The simulation with EMIC waves improves the dynamics of ultrarelativistic fluxes and reproduces the formation of the local minimum in the phase space density profiles. Key Points: Addition of EMIC waves improves the long‐term simulation of multi‐MeV electron dynamics Solar wind dynamic pressure provides better parameterization of EMIC wave presence than Kp, Dst, and AE indices and solar wind velocity Simulation with parameterized EMIC waves reproduces a phase space density deepening minimum